Aplicação do ultrassom e ácidos orgânicos na sanitização de morangos (fragaria x Ananassa Duch.) - Alvarenga, Priscila Donatti Leão (2018)
Consumers are interested in the consumption of safe foods with long storage time and that do not show changes in nutritional and sensory quality after processing. Thus, the consumption of fresh cut fruits and vegetables has grown. For these foods, the sanitization step is considered the crucial step for microbiological control. Chlorinated compounds are the main sanitizing agents used. However, there are indications that these sanitizers when combined organic matter in the state of decomposition can cause the formation of by-products considered as toxic. Therefore, there is an interest in the study of sanitizers and alternative processes in the application of chlorinated compounds in fruits and vegetables. Among the proposed strategies, we have the application of acetic acid, peracetic acid and ultrasound. Organic acids have recognized antimicrobial action and do not produce by-products during their application. The use of ultrasound in food has been studied because it is a non-thermal method that reduces the microbial load of food. It is a technology that generates high amplitude waves with low frequency, where the physical and chemical effects have the capacity to damage the cell wall of some microorganisms. Microbiological analyzes (aerobic mesophiles, molds and yeasts, coliforms at 35 °C and intentionally inoculated Escherichia coli), physico-chemical analyzes (pH, titratable total acidity, total soluble solids, ratio acidity, vitamin C, total anthocyanins and loss of mass) on days 1, 3, 6 and 9 of storage. Scanning electron microscopy was conducted too. Data were submitted to analysis of variance (ANOVA), regression analysis, Pearson correlation and Duncan test at 5% probability. It was observed that storage time significantly interfered with pH values, titratable total acidity, total soluble solids and total soluble solids ratio and titratable total acidity (p<0.05). Treatments promoted reduction of the vitamin C content in the samples between the 1st day and the 3rd day, except in the sample treated with ultrasound. After the 6th day, there was a reduction of vitamin C content in all treatments, a fact that may be related to plant tissue senescence. Anthocyanin values did not change in relation to treatment or time and had a general average of 13.47 mg of anthocyanin/100 g of strawberries. The mass loss was not significantly affected by the applied treatments (p>0.05). The counts of aerobic mesophilic and coliform at 35°C did not present a significant difference (p<0.05) between the applied sanitization treatments. The treatments promoted reduction between 1.09 to 2.48 log of CFU/g and 0.89 and 1.45 log of CFU/g of aerobic mesophilic and coliform at 35 °C, respectively. For molds and yeasts it was observed that there was a significant difference in relation to treatment and time (p <0.05). Reductions between 0.76 and 1.99 log CFU/g were observed in the count of molds and yeast. Ultrasound treatments in combination with peracetic acid and acetic acid allowed a decimal reduction of molds and yeasts (p <0.05). There was no significant difference between treatment with sodium hypochlorite and ultrasound (p<0.05). All evaluated treatments promoted reduction of the E. coli count (p <0.05). The treatments with peracetic acid, acetic acid, sodium hypochlorite, ultrasound and ultrasound combined with acetic acid promoted statistically equal reductions (p> 0.05). Scanning electron microscopy revealed fragmented E. coli cells due to treatment with acetic acid and ultrasound. In the treatments with peracetic acid and this combined to the ultrasound one can observe reduced number of microorganisms in the surface of the strawberry, alteration of the morphology and fragments of cells of E. coli. Thus, the combination of ultrasound and peracetic acid may be an alternative to ensure microbiological safety without causing significant changes in the physico-chemical characteristics of strawberries.